PENDIDIKAN KESEHATAN REPRODUKSI PADA REMAJA : STUDI DESKRIPTIF DI PLKB MEURAXA - Safrizan Safrizan; Rahmat Akbar (JOURNAL OF HEALTHCARE TECHNOLOGY AND MEDICINE, 2026)
Reproductive health education for adolescents is a promotive and preventive effort to improve adolescents’ knowledge and awareness of reproductive health. This community service activity aimed to increase adolescents’ understanding through health education at PLKB Meuraxa. The methods used were lectures, material presentations, and interactive discussions. The results showed an improvement in adolescents’ understanding of reproductive health, puberty, reproductive organ hygiene, and prevention of risky sexual behavior. Reproductive health education is expected to help adolescents apply healthy and responsible lifestyles.